Pharyngeal Carriage of Beta-Haemolytic Streptococcus Species and Seroprevalence of Anti-Streptococcal Antibodies in Children in Bouaké, Côte d’Ivoire - Pacôme Monemo; Nadia Demba; Fidèle S. Touré; Adjartou Traoré; Christelle Avi; Micheline A. N’Guessan; Juste O. Tadet; Arthur R. Gobey; Augustin E. Anoh; Abdoulaye Diarrassouba; Marie N. Tuo; Amadou Cissé; et al. (Tropical Medicine and Infectious Disease, 2020)
The pharynx of the child may serve as a reservoir of pathogenic bacteria, including beta-haemolytic group A streptococci (GAS), which can give rise to upper airway infections and post-streptococcal diseases. The objective of this study was to determine the prevalence of beta-haemolytic Streptococcus spp. in pharyngeal samples stemming from children aged 3–14 years in Bouaké, central Côte d’Ivoire. Oropharyngeal throat swabs for microbiological culture and venous blood samples to determine the seroprevalence of antistreptolysin O antibodies (ASO) were obtained from 400 children in March 2017. Identification was carried out using conventional bacteriological methods. Serogrouping was performed with a latex agglutination test, while an immunological agglutination assay was employed for ASO titres. The mean age of participating children was 9 years (standard deviation 2.5 years). In total, we detected 190 bacteria in culture, with 109 beta-haemolytic Streptococcus isolates, resulting in an oropharyngeal carriage rate of 27.2%. Group C streptococci accounted for 82.6% of all isolates, whereas GAS were rarely found (4.6%). The ASO seroprevalence was 17.3%. There was no correlation between serology and prevalence of streptococci (p = 0.722). In conclusion, there is a high pharyngeal carriage rate of non-GAS strains in children from Bouaké, warranting further investigation.